2001
DOI: 10.1016/s0014-5793(01)03039-3
|View full text |Cite
|
Sign up to set email alerts
|

Dioxin induces a novel nuclear factor, DIF‐3, that is implicated in spermatogenesis

Abstract: 2,3,7, dioxin), a member of a class of environmental pollutants represented by polychlorinated dibenzo-p-dioxins and dibenzofurans, is one of the most toxic artificial compounds ever developed. In this study, we identified a novel TCDD target gene, DIF-3 (dioxin inducible factor-3), by cDNA representational difference analysis. DIF-3 protein is a nuclear factor and possesses a zinc-finger motif at its N-terminus. High DIF-3 mRNA expression in the testes was demonstrated by Northern blot analysis and abundant D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
34
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…Given that GGNBP2 is a conserved zinc finger protein in human and mouse,3, 4, 13 it presumptively has similar functions in regulation of spermatogenesis in humans. A recent comprehensive analysis revealed that sperm counts continually and significantly declined over a 38‐year period in men from Western countries 42.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that GGNBP2 is a conserved zinc finger protein in human and mouse,3, 4, 13 it presumptively has similar functions in regulation of spermatogenesis in humans. A recent comprehensive analysis revealed that sperm counts continually and significantly declined over a 38‐year period in men from Western countries 42.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism by which dioxins impair spermatogenesis remains elusive. The expression of GGNBP2 has been demonstrated to be regulated by dioxin and GGNBP2 plays critical roles in spermatocyte meiosis and spermatid differentiation 4, 13. Thereby, it would be worthwhile in future studies to investigate whether GGNBP2 is a factor that associates with dioxin‐induced reproductive toxicity by interfering with spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of several genes, such as wings apart-like (WAPL) [14] and dioxin inducible factor-3 (DIF-3) [20], are regulated by TCDD administration. We can evaluate the effects of TCDD on the reproductive system by using these genes as expression standards.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that TCDD mediates its toxicity by constructing an AhR (aryl hydrocarbon receptor) and Arnt (aryl hydrocarbon receptor nuclear translocator) [15,16] complex between TCDD, that binds to the XRE (xenobiotic responsive element) sequence, which is located upstream of the dioxinresponsive genes, such as cytochrome P450 gene family, whose expression it upregulates. Recently, the cDNA for DIF-3 (dioxin inducible factor-3), which has a zinc finger motif, was cloned from mouse testis, and the expression was induced by dioxin treatment [17]. This gene thus could be a candidate as a biomarker to assess the toxicity of dioxin for the reproductive system.…”
mentioning
confidence: 99%